Effect of Different Component Values on 3- Stage Type-B Pulse Forming Network (International Journal of Engineering and Computer Science, 2014)
The line-type pulse generators are generally not produce as rectangular as the pulse generated by the hard-tube pulser. Moreover, the line-type pulse generator usually has a longer rise and fall time and has oscillation on the top of the pulse. Overshoot on the leading and trailing edges is familiar kind of distortion. These distortions of the pulse shape may be reduced by special network design. This work proposes the design of a 3-stage type-B pulse forming network and the performance of the design have been studied to evaluate the effect of output parameters for different load resistance values. The results are evaluated for different load resistance value while keeping the other components value as static. The characteristic impedance for the design was selected as 50Ω. In this paper, input applied voltage of 1KV is considered for the design and result evaluation purposes. The results are evaluated to see the effect of load currents (IZ), capacitor currents (IC), inductor currents (IL) and capacitor voltages (CV) for different load resistances